Cyclic response of RC composite bridge columns with precast PP-ECC jackets in the region of plastic hinges. (1st August 2019) - Zhang, Rui; Meng, Qingli; Shui, Qingjun; He, Wei; Chen, Kexu; Liang, Minfei; Sun, Zhaoyang
Abstract: ECC characterized by its tensile strain-hardening behavior, high compressive strain and damage tolerance capacity is an ideal material in the plastic hinges of RC bridge columns. The existing studies have investigated the seismic performance of RC bridge columns with total ECC plastic hinges and indicated that was enhanced significantly. However, because the cost of ECC is high and total ECC plastic hinge still needs quite amount, it is difficult to be used in the engineering applications. In this study, the precast PP-ECC jackets were proposed to fabricate the ECC/RC composite section in the region of plastic hinges in RC bridge columns. The design theory of PP-ECC jackets was proposed and a total of four scaled RC bridge columns were designed and fabricated. One specimen was RC column for reference, and another one was a RC column with total ECC plastic hinge. The rest of two columns used precast PP-ECC jackets with two different thicknesses. The unilateral cyclic loading tests were performed. It was found that the RC columns using PP-ECC jackets exhibited superior and comparable structural performance compared to normal RC column and RC column with total ECC plastic hinge, respectively.